How a tiger became a pussycat : a comparison of economic development of Taiwan and Mainland China - Antić, Miljenko, inženjer građevinarstva (Array, 2020)
Based on capitalism and socialist measures, Taiwan not only achieved better results than Mainland China during the 1949-91 period, but also better results than any other country in the world in promoting economic growth. A lack of market was the main disadvantage of Mainland China during this period of time. However, its successful pro-market reforms and unsuccessful reforms in Taiwan (based on privatization), reversed the tide. During the last quarter of the century, Mainland China has more efficient economic system than Taiwan. As a result, Mainland China became the world’s leading economic power in 2014 and it continues to have higher rates of growth than Taiwan.